A Gift or a Waste? Quintavalle, Surplus Embryos and the Abortion Act 1967. Issue 2 (4th May 2017) - Cherkassky, Lisa
Abstract : The destruction of an embryo must be justified in law. This is to prevent frivolous wastage and to show the respect afforded by the Warnock Report (1984). For example, embryonic destruction during pregnancy is underpinned by the Abortion Act 1967, and embryonic destruction during fertility treatment is regulated by the Human Fertilisation and Embryology Act 1990. However, following the appeal decision in R (Quintavalle) v Human Fertilisation and Embryology Authority (and Secretary of State for Health) [2005] 2 A.C. 561, embryos can now be created for a bone marrow tissue match to a sick sibling under the Human Fertility and Embryology Act 1990 according to the subjective desires of the mother. This opens the door to the first example of embryonic destruction on unique social-eugenic grounds with no clear lawful justification. It is argued that these embryos should be afforded a unique destruction provision under an amended version of section 1(1)(a) of the Abortion Act 1967 in light of their 'social-eugenic' nature. This would protect the Human Fertilisation and Embryology Authority from accusations of undercover eugenic practices and reinstate the respect shown towards embryos in law.